PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP CUSTOMER TRUST DAN CUSTOMER LOYALTY PADA BANK BRI CABANG PEKANBARU IMAM MUNANDAR. - Harry Febriyan; Zulkarnain Zulkarnain; Lilis Sulistyowati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aimed to analyze the influence of Customer Relationship Management (CRM) to the Customer Trust and Customer Loyalty at Bank BRI Branch pekanbaru Imam Munandar. Quantitative research was conducted on a population of customer deposits with a total sample of 150 customers, Savings, deposits and current accounts using proportional stratified random sampling method. Data collection techniques used in this study is a survey and observation using data analysis techniques Path Analysis with SPSS. The results showed that all dimensions of CRM: People, Process, and Technology in partial significant effect on Customer Trust. Customer Trust has a significant influence on Customer Loyalty. While the overall CRM significant effect on Customer Loyalty.